Post-operative Giant Pseudomeningocele Following L3-L4 Discectomy: A case report and Literature Review - Subedi, Ram Prasad; Yogi, Nikunja; Thulung, Suraj; Shrestha, Pratyush; Bishokarma, Suresh; Koirala, Sagar (Nepal Journal of Neuroscience, 2025)
After Lumbar spine surgery many of the patients improve but few develop post-operative lumbar giant pseudomeningocele causing symptomatic trouble in rare cases. In our case a 21-year-old male who was operated in other hospital for symptomatic Prolapsed lumber intervertebral Disc where microdiscectomy was done. After 5 months he developed  symptomatic pseudomeningocele over the operative scar area, confirmed by clinical examination and Imaging.  Due to headache and annoyable swelling in the lower back, L3-L4 Laminectomy with duroplasty with dural sealant fibrin glue with Lumbar drain was performed. His post operative period was uneventful, His giant pseudomeningocele resolved and he was discharged on 11th post-operative day.